2008
DOI: 10.1530/eje-08-0082
|View full text |Cite
|
Sign up to set email alerts
|

Early onset of polyglandular failure is associated with HLA-DRB1*03.

Abstract: Objectives: Polyglandular failure or autoimmunity (PGA) involves at least two endocrine diseases. Several genes may play a role in its etiology. This study analyzed 1) whether HLA-DRB1, HLA-DQB1, and MHC class I chain-related gene A (MICA) polymorphisms are associated in PGA and 2) whether PGA patients display stronger associations with these immune genes than patients with monoglandular autoimmunity (MGA). Design: Association study. Methods: HLA-DRB1, HLA-DQB1, and MICA alleles were analyzed in 73 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
5

Year Published

2009
2009
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 22 publications
1
12
0
5
Order By: Relevance
“…Not unexpectedly, the locus showing the strongest linkage with APS3v was the HLA class II locus (15). These data are supported by other studies (10,12,16). Detailed analysis of the HLA class II locus demonstrated that the major HLA haplotype contributing to the shared susceptibility to T1D and AITD was DR3-DQB1*0201, with DR3 conferring most of the shared risk (11,17).…”
supporting
confidence: 80%
“…Not unexpectedly, the locus showing the strongest linkage with APS3v was the HLA class II locus (15). These data are supported by other studies (10,12,16). Detailed analysis of the HLA class II locus demonstrated that the major HLA haplotype contributing to the shared susceptibility to T1D and AITD was DR3-DQB1*0201, with DR3 conferring most of the shared risk (11,17).…”
supporting
confidence: 80%
“…It codes for a protein with a shortened transmembrane segment lacking its cytoplasmic tail. Compared to healthy controls, frequency of the MICA 5.1 allele and the A5.1/A5.1 genotype was increased in patients with PAS II (38), indicating that the MICA microsatellite polymorphism may contribute to genetic susceptibility to PAS. Frequencies of the MIC-A5.1 allele were not significantly different in HLA-DRB1*03-carriers and non-carriers, suggesting that the risk conferred by MICA association might be independent of HLA-DRB1*03 risk.…”
Section: Pas Type IImentioning
confidence: 89%
“…[54] несколько отличались от предыду-щих: частота гаплотипов DR3-DQB1*0201 и DR4-DQB1*0302 была увеличена у пациентов с АПС2 по сравнению с кон-трольной группой, но только DR4-DQB1*0302 чаще встречался у пациентов с АПС3. Эти результаты отличаются от результа-2/2011 Сахарный диабет тов других исследований, которые показали, что как гаплотип DR3-DQB1*0201, так и гаплотип DR4-DQB1*0302 способство-вали предрасположеннос ти к АПС3 [53,55,58,65]. Недавние исследования в Германии показали еще раз, что HLA-DR3 в значительной степени связан с АПС3 [65].…”
Section: в предрасположенность к аиз щжunclassified
“…Эти результаты отличаются от результа-2/2011 Сахарный диабет тов других исследований, которые показали, что как гаплотип DR3-DQB1*0201, так и гаплотип DR4-DQB1*0302 способство-вали предрасположеннос ти к АПС3 [53,55,58,65]. Недавние исследования в Германии показали еще раз, что HLA-DR3 в значительной степени связан с АПС3 [65].…”
Section: в предрасположенность к аиз щжunclassified